A Multinational Study of Acute and Long‐Term Outcomes of Type 1 Galactosemia Patients Who Carry the S135L (c.404C > T) Variant of GALT - Katler, Q (2022)
Patients with galactosemia who carry the S135L (c.404C > T) variant of galactose-1-P uridylyltransferase (GALT), documented to encode low-level residual GALT activity, have been under-represented in most prior studies of outcomes in Type 1 galactosemia. What is known about the acute and long-term outcomes of these patients, therefore, is based on very limited data. Here, we present a study comparing acute and long-term outcomes of 12 patients homozygous for S135L, 25 patients compound heterozygous for S135L, and 105 patients homozygous for two GALT-null (G) alleles. This is the largest cohort of S135L patients characterized to date. Acute disease following milk exposure in the newborn period was common among patients in all 3 comparison groups in our study, as were long-term complications in the domains of speech, cognition, and motor outcomes. In contrast, while at least 80% of both GALT-null and S135L compound heterozygous girls and women showed evidence of an adverse ovarian outcome, prevalence was only 25% among S135L homozygotes. Further, all young women in this study with even one copy of S135L achieved spontaneous menarche; this is true for only about 33% of women with classic galactosemia. Overall, we observed that while most long-term outcomes trended milder among groups of patients with even one copy of S135L, many individual patients, either homozygous or compound heterozygous for S135L, nonetheless experienced long-term outcomes that were not mild. This was true despite detection by newborn screening and both early and life-long dietary restriction of galactose. This information should empower more evidence-based counseling for galactosemia patients with S135L.